PENGARUH METODE BERMAIN DALAM PEMBELAJARAN ATLETIK TERHADAP HASIL BELAJAR JALAN CEPAT SISWA SMP NEGERI 2 KOTO BARU - Septi Yani; Alchonity Harika Fitri; Muhammad Sukron (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The quality of athletics learning, particularly race walking, is strongly influenced by the instructional methods implemented by teachers. Conventional teacher-centered approaches often reduce students' participation, motivation, and mastery of basic movement skills. This study aimed to examine the effect of the play method on race walking learning outcomes among eighth-grade students at SMP Negeri 2 Koto Baru. A quantitative approach was employed using a Pre-Experimental One-Group Pretest–Posttest Design. The participants consisted of 30 eighth-grade students selected through purposive sampling. Data were collected using a race walking performance assessment and student activity observation sheets. Data analysis included normality testing, homogeneity testing, and paired-samples t-test. The findings revealed that students' mean learning outcome score increased from 57.50 on the pretest to 90.33 on the posttest. The paired-samples t-test showed a significance value of 0.000 (p < 0.05), indicating that the play method significantly improved students' race walking learning outcomes. The play-based learning approach also enhanced students' engagement, motivation, confidence, and mastery of basic race walking techniques. The novelty of this study lies in integrating structured play activities into athletics instruction for junior high school students, demonstrating that enjoyable and student-centered learning effectively improves psychomotor achievement. These findings suggest that the play method can serve as an alternative instructional strategy for improving athletics learning quality in physical education.